2005
DOI: 10.4049/jimmunol.175.2.796
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Presentation of the Long-Lived Lymphocytic Choriomeningitis Virus Nucleoprotein Does Not Require Neosynthesis and Is Enhanced via Heat Shock Proteins

Abstract: Many viral proteins that contain MHC class I-restricted peptides are long-lived, and it is elusive how they can give rise to class I epitopes. Recently, we showed that direct presentation of an epitope of the long-lived lymphocytic choriomeningitis virus nucleoprotein (LCMV-NP) required neosynthesis in accordance with the defective ribosomal products hypothesis. In this study, we report that LCMV-NP can be cross-primed in mice using either LCMV-NP-transfected human HEK293 or BALB/c-derived B8 cells as Ag donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 51 publications
8
91
1
Order By: Relevance
“…1C). We evaluated if the infected LyUV-ADC can supply LCMV antigens for cross-presentation when compared with HEK-NP cells [7,8]. By employing NP396-specific CTL, we confirmed that the infected LyUV-ADC supplied sufficient levels of LCMV-NP for cross-presentation to take place (Fig.…”
Section: Characterization Of Lcmv-infected Uv-irradiated Adcmentioning
confidence: 76%
See 4 more Smart Citations
“…1C). We evaluated if the infected LyUV-ADC can supply LCMV antigens for cross-presentation when compared with HEK-NP cells [7,8]. By employing NP396-specific CTL, we confirmed that the infected LyUV-ADC supplied sufficient levels of LCMV-NP for cross-presentation to take place (Fig.…”
Section: Characterization Of Lcmv-infected Uv-irradiated Adcmentioning
confidence: 76%
“…In this study, we employed the LCMV infection model to study how crosspresentation of multiple epitopes translates when studying cross-priming. We used LyUV treatment of the ADC because it fully inactivated the virus and allowed for efficient NP396 crosspresentation similar to HEK-NP cells [7,8]. We initially expected that GP33 would fail to cross-present because it is located in the signal peptide of LCMV-GP [12], but it was cross-presented with low efficiency, probably due to its exceptional long half-life of 6 h [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations